Comparison of blood loss between saline infiltration and no infiltration dissection during vaginal prolapse surgery -randomized controlled trial - Shemeena P Sayed; Gowri Dorairajan (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2021)
Background: Pelvic organ prolapse is common among women above 50 years. The literature on intraoperative interventions to reduce blood loss during vaginal prolapse surgery is very limited. Vasopressin infiltration, shown to reduce blood loss during non-descent vaginal hysterectomy, has adverse effects. Objectives: To compare blood loss between saline hydrodissection and no infiltration native tissue surgery for pelvic organ prolapse. Methods and Materials: Settings and Design: Randomized controlled trial conducted in the Department of Obstetrics and Gynaecology of a tertiary care teaching hospital in South India. Women with stage 2 or higher prolapse involving at least two components, undergoing vaginal hysterectomy and reconstruction were included. Block randomization was used to study 22 women in each group. 60-80ml saline was instilled in sub-mucosa before vaginal wall dissection. The mean actual, average, and clinically estimated blood loss in the two groups during surgery was compared by Mann Whitney test. Results: The mean age, stage of prolapse, and duration of surgery were comparable in the two groups. The Saline group had significantly higher parity, lower preoperative haemoglobin and a higher mean Ba point. Average blood loss was significantly lower in the saline dissection group 294.8 (+96.87) ml compared to 507.31(+348.37) ml in the no infiltration group (z=-2.04 p=0.04).  Conclusions: Saline dissection significantly reduces blood loss by approximately 200 ml in comparison to dissection with no infiltration without increasing any intra-operative and post-operative complications. We recommend its use during vaginal surgery for stage 2 or more uterovaginal prolapse involving more than one component  Key Messages: saline infiltration in vaginal submucosa before dissection significantly reduces blood loss (by 200ml) compared to no infiltration traditional dissection, during vaginal prolapse surgery with native tissue. Clinical Trial Registry of India (CTRI) registration reference number: CTRI/2017/10/010193.